Industrial Teesside, Lives and Legacies A post-industrial geography - Warren, Jonathan (Springer International Publishing, 2018)
This book evaluates the consequences of economic, social, environmental and cultural change on people living and working within Teesside in the North-East of England. It assesses the lived experiences, working lives, health and cultural perspectives of residents and key stakeholders in the wake of serious de-industralisation in the region. The narrative is embedded within the long-term industrial history of Stockton: an area once dominated by steel, coal and chemical industries. This past still continues to shape its future and influences the ways in which that future is conceived and envisioned. The author explores a 'biography of place' analytical framework to offer a holistic view of the area, which considers the interaction between the social, economic, cultural, visual and environmental legacy of the community, which is firmly grounded in the past, present and future prospects of those who live and work there.